2013
DOI: 10.1080/07391102.2013.833858
|View full text |Cite
|
Sign up to set email alerts
|

A study of the structural properties and thermal stability of human Bcl-2 by molecular dynamics simulations

Abstract: The anti-apoptotic B-cell lymphoma 2 (Bcl-2) protein interacts with several proteins that regulate the apoptotic properties of cells. In this research, we conduct several all-atom molecular dynamics (MD) simulations under high-temperature unfolding conditions, from 400 to 800 K, for 25 ns. These simulations were performed using a model of an engineered Bcl-2 human protein (Bcl-2-Δ22Σ3), which lacks 22 C-terminal residues of the transmembrane domain. The aim of this study is to gain insight into the structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 74 publications
(105 reference statements)
1
5
0
Order By: Relevance
“…The results showed that the TM domains reached equilibrium and were likely to be correctly modeled; whereas the regions outside the membrane still remained mobile (also shown by the RMSF values). This is a general occurrence for TM proteins ( Nugent and Jones, 2012 ) and it has been reported for other proteins, such as Bcl-2 ( Ilizaliturri-Flores et al, 2013 ).…”
Section: Discussionsupporting
confidence: 60%
“…The results showed that the TM domains reached equilibrium and were likely to be correctly modeled; whereas the regions outside the membrane still remained mobile (also shown by the RMSF values). This is a general occurrence for TM proteins ( Nugent and Jones, 2012 ) and it has been reported for other proteins, such as Bcl-2 ( Ilizaliturri-Flores et al, 2013 ).…”
Section: Discussionsupporting
confidence: 60%
“…Similar results have been reported in previous reports. The conformational changes observed, showing the propensity of FLD to fold on itself and to move towards the core are, not dependent on the force-field or program used for MDS analysis [19,20]. When FLD approaches the central core, Bcl-2 and Bcl-2ΔTM become more compact.…”
Section: Discussionmentioning
confidence: 99%
“…Further, several Caspase-3 cleavage sites are present within the FLD. Phosphorylation and/or caspase-cleavage are important in the activity regulation of Bcl-2 [18,19]. The FLD structure has not been resolved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are no general factors for determining thermostability and it is obvious that different proteins gain their thermostability owing to different combinations of the above factors. To attain a general understanding, many experiments and theoretical researches have concentrated on the folding-unfolding process of various proteins depending on temperature (Day, Paschek, & Garcia, 2010;Grottesi et al, 2002;Ilizaliturri-Flores, Correa-Basurto, Benítez-Cardoza, & Zamorano-Carrillo, 2014;Meharenna & Poulos, 2010;Priyakumar, 2012;Priyakumar, Ramakrishna, Nagarjuna, & Reddy, 2010;Tang & Liu, 2007). However, microscopic structures of proteins and trapping of dynamic intermediates in this process have always been intractable because of the tiny tempo-spatial scales.…”
Section: Introductionmentioning
confidence: 99%